Great Chalfield Manor
The hall fireplace, seen from above the screened passage, shows the archway leading to stairs from which the apartment above is reached. Early fireplaces were of generous proportions in order to burn timber, which was more plentiful, and more pleasant than burning coal. All the furnishing is modern; the contemporary furniture would consist of benches and a long central table at the head of which sat the Lord of the Manor. In greater houses there would be a separate High Table on a raised platform or dais.